Exploring the impact of post-high school experiences on the social identities of newly graduated girls - Haffajee, Natasha (Graduate School of Business (GSB), 2025)
The transition from high school to adulthood represents a critical juncture in the lives of young women, particularly for those from marginalised communities in Cape Town, South Africa. This period is marked by significant shifts in social identity, yet existing literature largely overlooks the sudden social identity changes (SSIC) that occur in non-traumatic contexts, such as this transition. Most studies on identity development have focused on gradual changes and their impact on individual well-being, leaving a gap in understanding how young women navigate abrupt identity transformations during key life stages. This research addressed this gap by examining how newly graduated girls experience SSIC and how these changes impact their ability to exercise agency in resisting the risk of becoming NEET (Not in Employment, Education, or Training). Using hermeneutic phenomenology, the study delved into the lived experiences of these young women, highlighting the complex interplay of socioeconomic status, gender expectations, and the availability of social support systems, such as family, peers, and community networks. These factors significantly influenced the degree of agency exercised by the participants as they navigated their post-high school transitions. The findings contribute to the theoretical understanding of SSIC by challenging existing categorisations of identity change, particularly by emphasising the role of perceived self-efficacy and control in shaping these experiences. Contrary to traditional views of identity change as externally driven, this study reveals that these young women actively engage in the process, drawing on their resilience and support networks to assert their agency. In terms of social contribution, the research offers practical recommendations for developing targeted interventions that foster supportive environments, enhance resilience, and empower young women to navigate their transitions with confidence and determination. These insights are crucial for policymakers, educators, and community leaders aiming to support young women in marginalised communities as they transition from high school to adulthood, ensuring they are equipped to overcome challenges and seize opportunities.